Anatomy and Connectivity of the Torus Longitudinalis of the Adult Zebrafish - Folgueira, Mónica; Riva-Mendoza, Selva; Ferreño-Galmán, Noelia; Castro, Antonio; Bianco, Isaac H.; Anadón, Ramón; Yáñez, Julián (Frontiers in Neural Circuits, 2020)
This study describes the cytoarchitecture of the torus longitudinalis (TL) in adult zebrafish by using light and electron microscopy, as well as its main connections as revealed by DiI tract tracing. In addition, by using high resolution confocal imaging followed by digital tracing, we describe the morphology of tectal pyramidal cells (type I cells) that are GFP positive in the transgenic line Tg(1.4dlx5a-dlx6a:GFP)ot1. The TL consists of numerous small and medium-sized neurons located in a longitudinal eminence attached to the medial optic tectum. A small proportion of these neurons are GABAergic. The neuropil shows three types of synaptic terminals and numerous dendrites. Tracing experiments revealed that the main efference of the TL is formed of parallel-like fibers that course within the marginal layer of the optic tectum. A toral projection to the thalamic nucleus rostrolateralis is also observed. Afferents to the TL come from visual and cerebellum-related nuclei in the pretectum, namely the central, intercalated and the paracommissural pretectal nuclei, as well as from the subvalvular nucleus in the isthmus. Additional afferents to the TL may come from the cerebellum but their origins could not be confirmed. The tectal afferent projection to the TL originates from cells similar to the type X cells described in other cyprinids. Tectal pyramidal neurons show round or piriform cell bodies, with spiny apical dendritic trees in the marginal layer. This anatomical study provides a basis for future functional and developmental studies focused on this cerebellum-like circuit in zebrafish.